Therapeutic Response to Corticosteroids Remains a Valid Approach to Initial Management of Children With Idiopathic Nephrotic Syndrome - Narla, Deepti; Swiatecka-Urban, Agnieszka (Frontiers in Pediatrics, 2020)
Response to corticosteroids has been widely adopted for the initial management of pediatric patients with idiopathic nephrotic syndrome (INS) while kidney biopsy has been reserved for patients who failed to respond. The approach was based on the results of studies conducted in the 1960s and 1970s. The studies found that corticosteroid-responsive minimal change disease (MCD) was the most frequent diagnosis in INS patients. In more recent years, studies have reported increased frequency of focal segmental glomerulosclerosis (FSGS) and primary corticosteroid resistance without a corresponding increase of FSGS. It became unclear whether withholding kidney biopsy before treatment with corticosteroids is still the best management practice. We performed a retrospective chart review at the UPMC Children’s Hospital of Pittsburgh and identified patients who were referred for evaluation of edema or proteinuria between 2002 and 2014. We identified 114 pediatric patients with INS who were treated initially with a corticosteroid (prednisone or prednisolone) 2mg/kg (max 60 mg)/day for 8 weeks and had not received a corticosteroid-sparing agent before completing at least 8 weeks of the initial therapy. Corticosteroid resistance in pediatric INS patients was independently associated with the black race, older age at presentation (> 8 years), and female sex. The majority of blacks who were resistant to corticosteroids had a tissue diagnosis of MCD. Among the whites who were steroid-resistant, MCD and FSGS were diagnosed in similar proportions of cases. Thus, the tissue diagnosis in could not predict the response to corticosteroids. Nineteen percent of whites with FSGS were steroid-sensitive and none of the blacks with FSGS responded to corticosteroids. These data suggest that the histologic diagnosis of FSGS could not rule out response to corticosteroids, at least, in the white patient population. In summary, our data demonstrate that at this time, the therapeutic response to corticosteroids continues to be a valid approach for the initial evaluation and therapy of children diagnosed with INS at our center. Future studies should evaluate the mechanisms of changing characteristics of pediatric INS. The specific role of patient demographics, ethnicity, as well as genetic and environmental factors could be evaluated by a prospective, multicenter study.